ISOLATION, IDENTIFICATION AND CHARACTERIZATION OF ENDOPHYTIC FUNGI WHICH ISOLATED FROM SANSEVIERIA ROXBURGHIANA PLANT - V. Manikandan, Dr.D.Arvind Prasanth (South Eastern European Journal of Public Health, 2025)
Endophytic microorganisms are lives in inside of the plant tissues without causing any infections or diseases in the plant. It may be transferred from environment to plant and plant bodies by some natural actions. A plant associated fungi are rich biodiversity group of microorganisms that lives in plant with asymptomatic conditions. It promotes plant growth by production of secondary metabolites. It also enhances the plant resistant nature against of insects, pest, biotic, abiotic stresses and against of some bacterial plant pathogens. The endophytic fungi can synthesis medically important components that involved in cancer treatment, diabetic and some diseases which caused by multidrug resistant bacteria. In this study, endophytic fungi which isolated from Sansevieria roxburghiana plant. A single potential fungal strain selected based on the antagonistic activity, used it for mass cultivation and identify the potential antimicrobial activity against of pathogenic bacteria.